2016
DOI: 10.1021/jacs.6b00982
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Specific 2-Cyanobenzothiazole Ligation

Abstract: The use of small, natural chemical reporters in conjunction with catalyst-free bioorthogonal reactions will greatly streamline protein labeling in cellular environment with minimum perturbation to their function. Here we report the discovery of a 2-cyanobenzothiazole (CBT) reactive peptide tag, CX10R7, from a cysteine-encoded peptide phage library using the phage-assisted interrogation of reactivity method. The fusion of CX10R7 with a protein of interest allows site-specific labeling of the protein with CBT bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 24 publications
1
50
0
Order By: Relevance
“…Recently,t he groups of Rao,C hin, and Lin achieved the bioorthogonal ligation of electron-deficient cyano groups, typically cyanobenzothiazole,w ith either an aminothiol or cysteine tag. [13] We also noted that nitrile moieties in some pharmaceuticals can interact reversibly with the thiol group in the active site of either target proteins or enzymes. [14] Inspired by these discoveries in the biological milieux, we hypothesized that thiols could reversibly activate weakly electrophilic aliphatic and aromatic nitriles at room temperature,generating am ore reactive thioimidate ester intermediate in situ.…”
mentioning
confidence: 89%
“…Recently,t he groups of Rao,C hin, and Lin achieved the bioorthogonal ligation of electron-deficient cyano groups, typically cyanobenzothiazole,w ith either an aminothiol or cysteine tag. [13] We also noted that nitrile moieties in some pharmaceuticals can interact reversibly with the thiol group in the active site of either target proteins or enzymes. [14] Inspired by these discoveries in the biological milieux, we hypothesized that thiols could reversibly activate weakly electrophilic aliphatic and aromatic nitriles at room temperature,generating am ore reactive thioimidate ester intermediate in situ.…”
mentioning
confidence: 89%
“…However, it should be noted that these nitriles are also of direct interest for their mild biocompatible condensation with N-terminal cysteines and related aminothiols. 2023 …”
mentioning
confidence: 99%
“…Inspired by these works, very recently,L in andc o-workers have found that the CBT ligationc ould also be appliedt ol abel internal Cys in as pecific peptides equence of VTNQECCSIPM (called CX10R7;F igure 4b). [84] They proposed that the central Cys surrounded with many polar and charged residues could stabilizet he thioimidate adduct. The optimal conditions to conduct the ligationr eaction between them weref ound to be PBS buffer (pH7.4) at 37 8Cf or 1h.U nder these reaction conditions, the second-order rate constant was about 17 m À1 s À1 , nearly two-fold faster than that observed in the CBT-Cys reaction.…”
Section: Site-specific Labeling Of Proteinsmentioning
confidence: 99%
“…Site-specific protein labeling with CBT.a)Schematic illustration of site-specific labeling of protein involving genetically encoded 1,2-aminothiols and CBT.b)Schematicillustration of protein labeling using peptide sequence-specific ligation between CBT and internal Cys. Reprinted with permissionfrom reference[84].…”
mentioning
confidence: 99%